(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2012)
Insurance actions has become a task of the vital foundations on which the international economy depends, where its presence helped in the development of economic resources in which human resource is considered the most important of these resources. Insurance companies play the biggest role in protecting this resource and minimizing the impact of the dangers that verify this condition.Human has worked hard to get rid of the dangers and its harm, and to devise many ways to prevent them. A risk management is considered within human’s creations in order to create a society with fewer negative risks impacts. On this basis, the researchers in this research deals with the issue of “Risk analysis in group insurance”. This research has been applied in the General Iraqi Insurance Company/ Department of Group Insurance, by testing one sample. The sample included the gross data about the number of policies and the realized losses for the year (2010) divided according to the four main categories of the group insurance and the months. The researchers used many statistical methods for testing the research hypotheses, between which the most important is finding Spearman’s correlation between the study variables and then using simple regression to extract the impact of the number of documents variable on the achieved losses. According to the achieved results, the researchers obtained many conclusions; some of the results are identical with the study hypotheses and other of the results is not identical. Finally, the researchers presented a set of recommendations and suggestions to the General Iraqi Insurance Company based on the results that have been reached.